Energy development and wildlife conservation in western North America - Naugle, David E.; SpringerLink (Online service). (Washington, DC Island Press, 2011)
Energy Development and Wildlife Conservation in Western North America offers a road map for securing our energy future while safeguarding our wildlife heritage.   Contributors show how science can help craft solutions to conflicts between wildlife and energy development by delineating core areas, identifying landscapes that support viable populations, and forecasting future development scenarios to aid in conservation design. The book frames the issue and introduces readers to major types of extraction quantifies the pace and extent of current and future energy development provides an ecological foundation for understanding cumulative impacts on wildlife species synthesizes information on the biological response of wildlife to development discusses energy infrastructure as a conduit for the spread of invasive species compares impacts of alternative energy to those of conventional development The final section calls for a shift away from site-level management that has failed to mitigate cumulative impacts on wildlife populations toward broad-scale planning and implementation of conservation in priority landscapes. The book concludes by identifying ways that decision makers can remove roadblocks to conservation, and provides a blueprint for implementing conservation plans.   Energy Development and Wildlife Conservation in Western North America is a must-have volume for elected officials, industry representatives, natural resource managers, conservation groups, and the public seeking to promote energy independence while at the same time protecting wildlife
Foreword -- Preface -- Acknowledgments -- PART I: ENERGY DEVELOPMENT AND THE HUMAN FOOTPRINT. 1. Introduction to Energy Development in the West; D.E. Naugle, H.E. Copeland -- 2. Geography of Energy Development in Western North America: Potential Impacts on Terrestrial Ecosystems; H.E. Copeland et al -- PART II: BIOLOGICAL RESPONSE OF WILDLIFE AND INVASIVE PLANTS TO ENERGY DEVELOPMENT. 3. Unifying Framework for Understanding Impacts of Human Developments on Wildlife; C.J. Johnson, Martin-Hugues St-Laurent -- 4. Sage-Grouse and Cumulative Impacts of Energy Development; D.E. Naugle et al -- 5. Effects of Energy Development on Ungulates; M. Hebblewhite -- 6. Effects of Energy Development on Songbirds; E.M. Bayne, B.C. Dale -- 7. Invasive Plants and Their Response to Energy Development; P.H. Evangelista et al -- 8. Wind Power and Biofuels: A Green Dilemma for Wildlife Conservation; G.D. Johnson, S.E. Stephens -- PART III: CONSERVATION BY DESIGN: PLANNING AND IMPLEMENTING SOLUTIONS. 9. Energy by Design: Making Mitigation Work for Conservation and Development; J.M. Kiesecker et al -- 10. Forecasting Energy Development Scenarios to Aid in Conservation Design; H.E. Copeland et al -- 11. Resource Policy, AdaptiveManagement, and Energy Development on Public Lands; M. Harm Benson -- 12. Community-Based Landscape Conservation: A Roadmap for the Future; G A. Neudecker et al -- Literature Cited -- Contributors -- About the Editor -- Index.
Electronic reproduction.
Keywords: Energy development -- Environmental aspects -- West (U.S.; Energy development -- Environmental aspects -- Canada, Western; Wildlife conservation -- West (U.S.); Wildlife conservation -- Canada, Western; Electronic books